Postoperative high-density lipoprotein cholesterol level: an independent prognostic factor for gastric cancer - Li, Chenxi; Fu, Yan; Li, Qiuwen; Yang, Xuhui; Wang, Wenying; Jin, Xin; Bian, Lihua; Zhao, Hui; Li, Donghui; Gao, Jie; Du, Nan; Peng, Liang (Frontiers in Oncology, 2022)
Objective The relationship between serum lipids and prognosis of gastric cancer has not been confirmed. Our purpose in the study was to investigate the associations between preoperative and postoperative serum lipids level and prognosis in patients with gastric cancer. Methods A retrospective study was performed on 431 patients who received radical (R0) gastrectomy from 2011 to 2013. Preoperative and postoperative serum lipids level were recorded. Clinical-pathological characteristics, oncologic outcomes, disease-free survival (DFS) and overall survival (OS) were collected. The prognostic significance was determined by Kaplan-Meier analysis and Cox proportional hazards regression model. Results There was no significant difference in DFS and OS according to preoperative serum lipids level. Regarding postoperative serum lipids level, compared to normal high-density lipoprotein cholesterol (HDL-C), low postoperative HDL-C level indicated a shorter OS (hazard ratio: 1.76, 99% confidence interval: 1.31–2.38; P=0.000) and a shorter DFS (hazard ratio: 2.06, 99% confidence interval: 1.55–2.73; P=0.000). However, other postoperative serum lipid molecules were not associated with DFS and OS. Conclusion Postoperative HDL-C might be an independent prognostic factor of gastric cancer.